Stability and rheological properties of water-in-oil (W/O) emulsions prepared with a soyasaponin-PGPR system - Yueying Pan; Yangyang Xu; Lijie Zhu; Xiuying Liu; Guoxiu Zhao; Shengnan Wang; Lina Yang; Tao Ma; He Liu (Future Foods, 2021)
This study aimed to develop an innovative water-in-oil (W/O) emulsion with soyasaponin (Ssa) and polyglycerol polyricinoleate (PGPR) as emulsifiers. The effects of the oil/water ratio and aqueous Ssa concentration on the stability of emulsions was investigated. The analyses performed include evaluations of the overall stability, droplet size, rheological analysis, and interfacial tension. Research indicated that the most stable W/O emulsion corresponded to a water/oil ratio of 30/70, and the stability could be further enhanced by increasing the concentration of Ssa and PGPR. In the case of a 1% (w/w) Ssa emulsifier, results indicate a decreased particle size, increased viscosity, and increased stability of the prepared W/O emulsions. Furthermore, with 1% Ssa, the Turbiscan stability index (TSI) value of the W/O emulsions at 3% PGPR was lower than that of pure 4% PGPR emulsions. The results clearly show that 3% PGPR and 1% Ssa exhibited a synergistic effect on the stability of the emulsion. Overall, this study establishes a method for constructing food-grade W/O emulsions, which has prospects for certain applications in delivering functional components.